Performance measurement framework for local authorities in Sarawak / Siti Mardinah Abdul Hamid - Abdul Hamid, Siti Mardinah (2019)
Local Authorities play a crucial role in the new environment setting. Most Local Authorities operate in a competitive environment; as such, it is important to optimize performances. It is believed that performance measurement tools can help to identify weaknesses, clarify objectives and strategies, and improve management processes. While many theories on performance measurement and performance management have been developed mainly for large organizations over the past two decades, few have been tailored for Local Authorities. In addition, this research highlights that these tools are difficult to adapt to Local Authorities. This research aims to identify and ascertain the important factors that influence the performance of Local Authorities in Sarawak and, in doing so, to propose a new Performance Measurement Framework that is relevant and applicable to the local setting. Qualitative and quantitative procedures are employed with 300 respondents from all divisions in Sarawak. There are twenty-three (23) Local Authorities involved in this study. These Local Authorities are under the Ministry of Local Government and Community Development Sarawak. The research methodology includes literature reviews, focus group interviews, expert opinion pilot test, Multivariate Test, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Pearson Correlation Analysis, Reliability Test, Validity Test and Multiple Regression Analysis. From the procedures, eight (8) factors were identified. They are Capabilities, Resources, Environment, Strategy, Process, Measure Analysis, Innovation and Learning and Emphasize Measure. The findings revealed that Innovation and Learning is the most important factor that influences performance for Local Authorities. Capabilities factor, resources factor, and environmental factors are significantly important factors that influenced performance Local Authorities in Sarawak. The findings suggest that Local Authorities need to analyze the external and internal environment through innovation before implementing Performance Measurement. Importantly, Local Authorities must manage their capabilities accordingly, optimize and develop resources, and adapt to changes in the environment. Thus, it is important for Local Authorities to manage performance with an appropriate framework, where the priorities are to consider capabilities, resources, and analysis of internal and external environments through innovation and learning.